Randomised controlled trial of human derived breast milk fortifier versus bovine milk fortifier on body composition in very preterm babies. (August 2022) - Uthaya, Sabita; Jeffries, Suzan; Andrzejewska, Izabela; Vasu, Vimal; Embleton, Nicholas D; Modi, Neena
Abstract: Background: Preterm infants receiving a diet of exclusive human milk compared to predominantly preterm formula have lower weight and non-adipose tissue mass by term. Human milk fortification is recommended. However, it is not known if the protein source affects body composition. Aims: To compare the effect of an exclusive human milk based diet (intervention) with a diet containing cow milk products (control) on body composition. Participants: Infants born below 30 weeks gestation. Study design: Randomised multicentre, open label, controlled trial. Infants preferentially received their own mother's milk. Infants were randomised to either an exclusive human milk diet (human milk formula to make up a shortfall in own mother's milk and human milk derived fortifier) or cow milk-based supplementation (preterm formula to make up a shortfall in own mother's milk and cow milk-based fortifier). Fortification began at an enteral intake of 150 ml/kg/day. Infants underwent whole-body magnetic resonance imaging at term. Primary outcome: Body composition (adipose tissue (ATM) and non-adipose tissue mass (N-ATM)) at term. Results: We randomly assigned 38 infants to intervention (n = 19) and control arms (n = 19). Primary outcomes were analysed in 15 infants in the intervention arm and 12 in the control arm. The estimates of the effect of the intervention following adjustment for length and sex, were non-significant (ATM (kg): 0.137, 95 % confidence interval (CI) -0.01, 0.29; N-ATM: −0.137; −0.01, 0.29). Conclusions: We identified no clinically relevant differences in body composition in preterm babies <30 weeks gestation receiving a macronutrient-equivalent exclusive human milk diet compared with a diet containing cow milk products. Highlights: No difference in body composition of preterm babies at term fed human milk versus cow milk diet No impact on body composition of source of protein in human milk fortifier No differences in feed tolerance, days of parenteral nutrition, exclusive breast-feeding at discharge No difference in length of stay, core outcomes or weight gain between birth and discharge